Relações de poder nos discursos do saber: antecedentes do dispositivo de popularização científica no Brasil e Uruguai - Gripp, Phillipp Dias (2016)
The present research takes as motif the meanings and historic changes in science and technology discourse of farming and agriculture specialty in the Platina Region. It is oriented by the rationale of perceiving how discourses about the topic, disseminated by journals specialized in farming and agriculture, deployed and enabled meanings to ideal readers during the 20th century in the Platina Region, specifically the Campanha Area in the state of Rio Grande do Sul, Brazil, and Uruguay. By other means, it is aimed at recognizing how power relations are exercised in the scope of scientific knowledge, enabling changes in the discourse of science public communication throughout such century. To answer to such questions, the present study is aimed at investigating the meanings and changes occurred on discursive regularities of periodicals that spread scientific knowledge in Brazil and Uruguay. Brazilian trimestral publications are edited under the responsibility of Associação Brasileira de Criadores Ovinos (Brazilian Association of Ovine Breeders; Bagé Rio Grande do Sul) and disseminated since 1942. From Uruguay, the monthly, commercial and independent magazine La Propaganda Rural (Montevideo-UY), published since 1901, was analyzed. The choice for such periodicals was made in view of the long production period, which allows the analysis of changes occurred on discourse during the 20th century and by their characterization as media products specialized in spreading information about farming and agriculture, including scientific and technologic knowledge of the area. The theoretical-methodological outlook is based on the scope of the Discourse Analysis of French origin, in order to determine which different discursive genres were produced by the periodicals and which discursive formations the enunciations are conditioned to throughout the decades. With such theoretical approach, we understand that the discourses about sciences obey the ideological formation of will to know and carry the concepts of scientific communication, scientific dissemination and scientific journalism as discursive formations. The concept of scientific popularization is adopted as a device that enables the exercise of power relations by non-specialists in the scope of sciences. The analysis taken noted the existence of four discursive genres: the qualifying, the prescriptive, the technical, particular to specialists elaboration, and the scientific-informative genre, produced by journalists. Furthermore, we understand that changes in meaning and enunciation constructions are associated to the beginning of the production of the periodicals by their journalist s editorial staff. Therewith, the discursive practice moves from an exclusive conditioning of scientific communication formation to a double conditioning of scientific communication and scientific journalism formations, period in which the beginnings of the use of the scientific popularization device is presented, by means of the scientific-informative genre.